C‐Reactive protein and insulin growth factor 1 serum levels during the menstrual cycle in adolescents with Type 1 diabetes. Issue 1 (3rd July 2015) - Codner, E.; Merino, P. M.; Martínez, D.; Lopez, P.; Godoy, C.; Iñiguez, G.; Cassorla, F.; Perez‐Bravo, F.
Abstract: Aims: To evaluate C–reactive protein, insulin growth factor 1 and lipid levels during the follicular and luteal phases in adolescents with Type 1 diabetes. Methods: Adolescents with Type 1 diabetes ( N  = 40) and healthy controls (C; N  = 43) were studied during the follicular and luteal phases of their menstrual cycles. C–Reactive protein, insulin growth factor 1 and lipid levels were measured. Results: Adolescents with Type 1 diabetes exhibited higher C–reactive protein levels than the C group during the follicular ( P  < 0.0001) and luteal phases ( P  < 0.01). The elevation of C–reactive protein levels was more pronounced in overweight adolescents with Type 1 diabetes than in adolescents in the C group. More adolescents with Type 1 diabetes were classified as having an elevated risk of cardiovascular disease (C–reactive protein > 3 mg/l) in the luteal phase than in the follicular phase (37.5% and 17.5%, respectively); half of the overweight adolescents with Type 1 diabetes in the luteal phase reached this level. BMI was the only significant factor affecting follicular and luteal phase C–reactive protein levels in adolescents with Type 1 diabetes. Lower insulin growth factor 1 levels were observed during both phases of the menstrual cycle in adolescents with Type 1 diabetes compared with controls. An elevation in insulin growth factor 1 levels in the luteal phase relative to the follicular phase was observed in controls, but not in adolescents with Type 1 diabetes. Luteal insulin growth factor 1 and C–reactive protein exhibited an inverse correlation ( r  = –0.4, P  = 0.01). Conclusions: Adolescents with Type 1 diabetes have higher C–reactive protein levels and lower insulin growth factor 1 levels relative to controls, especially during the luteal phase. Type 1 diabetes diminishes the natural elevation in insulin growth factor 1 levels observed during the luteal phase in controls. Excess weight exacerbates the subclinical inflammatory state observed during both phases of the menstrual cycle in adolescents with Type 1 diabetes.